Digging Beneath the Surface : An Exploration of the Net Benefits of Mining in Southern Africa - World Bank (World Bank, Washington, DC, 2019)
Mining has been central to the social and economic narrative of Southern Africa, and has been a key provider of investment, employment, government revenue and infrastructure in the region. In South Africa, the Johannesburg-Pretoria metropolitan area, which serves as the region's economic and financial hub, developed because of the local gold supply. In the early years, mining developed on the back of migrant workers from across Southern Africa who toiled in the mines under poor conditions. Many ex-miners suffer from vocational diseases to this day. While mining has helped build the economies of Southern Africa, it has come at social and environmental costs that cast a long shadow. Inequality is also high in many Southern African countries, suggesting that mining has not translated into inclusive growth. This report attempts to examine and weigh the various benefits and costs that mining has brought to the Southern Africa region. Data limitations are significant, restricting authoritative conclusions on whether the benefits from mining are positive or negative, on balance, for Southern African societies. The emphasis of this report is thus on taking stock of various benefits and costs associated with mining, while drawing on available information and thought experiments to highlight the potential trade-offs and how they affect stakeholder groups: workers, investors, governments, communities, and the rest of the economy. The countries this report focuses on are Botswana, Lesotho, Eswatini, Namibia, South Africa, Zambia, and Zimbabwe.